Armeniaspirol A: a novel anti‐Helicobacter pylori agent. Issue 2 (29th March 2021) - Jia, Jia; Zhang, Chongwen; Liu, Yaqi; Huang, Yanqiang; Bai, Yuefan; Hang, Xudong; Zeng, Liping; Zhu, Dongqing; Bi, Hongkai
Summary: Antibiotic resistance in Helicobacter pylori has been growing worldwide with current treatment regimens. Development of new compounds for treatment of H. pylori infections is urgently required to achieve a successful eradication therapy in the future. Armeniaspirols, a novel class of natural products isolated from Streptomyces armeniacus, have been previously identified as antibacterial agents against Gram‐positive pathogens. In this study, we found that armeniaspirol A (ARM1) exhibited potent antibacterial activity against H. pylori, including multidrug‐resistant strains, with MIC range values of 4–16 μg ml ‐1 . The underlying mechanism of action of ARM1 against H. pylori involved the disruption of bacterial cell membranes. Also, ARM1 inhibited biofilm formation, eliminated preformed biofilms and killed biofilm‐encased H. pylori in a dose‐dependent manner. In a mouse model of multidrug‐resistant H. pylori infection, dual therapy with ARM1 and omeprazole showed efficient in vivo killing efficacy comparable to the standard triple therapy, and induced negligible toxicity against normal tissues. Moreover, at acidic pH 2.5, ARM1 exhibited a much more potent anti‐ H. pylori activity than metronidazole. Thus, these findings demonstrated that ARM1 is a novel potent anti‐ H. pylori agent, which can be developed as a promising drug lead for treatment of H. pylori infections. Abstract : ARM1, a natural product isolated from S .  armeniacus, showed potent antimicrobial activity against H .  pylori both in vivo and in vitro. It is a possible drug candidate not only inhibiting planktonic growth and biofilm formation but also disrupting the mature biofilm by permeabilizing bacterial membranes.ARM1 might provide a promising drug lead for the development of anti‐ H .  pylori therapy.